A New Trend in Automatic Vehicle System - Vasumathi, G. (International Journal of Psychosocial Rehabilitation, 2018)
As of late framework has grown colossally however in like manner the mischance rate likewise expanded colossally. In the current framework just the human sees that the mishap has happened and they will call to the emergency vehicle and the scope of rescue vehicle to the spot is late because of that there is enormous loss of human life and for that an answer is raised by utilizing vibration sensor which faculties amid the event of mishap and utilizing GPS(global situating framework) the scope and the longitude of the position can be found and utilizing GSM(global framework for versatile correspondence) modem the position of the message can be send to the working focus and the working focus will have the GIS(geographical data framework) through which can discover the area effectively and they can call to the adjacent rescue vehicle and they will achieve the spot fastly and this all will occurs inside two minutes by this human life can be spared. On the off chance that this framework is executed we can spare upto sixteen people each hour on the grounds that generally the mishap will be little yet because of loss of more blood the individual will kick the bucket if the emergency vehicle achieve the spot inside couple of minutes of the mischance at that point the individual life can be spared effortlessly and the cost of framework is likewise low since these days the greater part of the vehicle is fitted with a GPS modem and just we need to get a GSM modem and a controller thus the framework will be taken a toll proficient.